(3bUjOI GdOQI GdjJjeIs - (3Ydj Hf eMeO Hf GdMSjf Hf jhSa Hf eMeO Hf YHO GdYRjR GdHSJj, CHh GdaJM,J (B400 (3g` s
(3ChdgG (B:s
(3RjGOI GdeA ai OfjGg fbUGf hQHMg ZjQ eMV GdNjQ NSQGf acd hLOGf NW dEKHGJ dg aEf eYfGg ai GdJMbjb abOGf s
(3BNQgG (B:s
(3NPgG ShGFQ GeKGdkG egPHI ajgG def jfHZi GdJHjGf JHjGf eG VQ MSGfgG hGdWHY UGFZgG Cf de jUagG bQjY GdTYQ MSGf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B685s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs